Molecularly proven mosaicism in phenotypically normal parent of a girl with Freeman–Sheldon Syndrome caused by a pathogenic MYH3 mutation. Issue 6 (21st March 2016) - Hague, Jennifer; Delon, Isabelle; Brugger, Kim; Martin, Howard; Abbs, Stephen; Park, Soo‐Mi
Abstract : We report a case of a female child who has classical Freeman–Sheldon syndrome (FSS) associated with a previously reported recurrent pathogenic heterozygous missense mutation, c.2015G > A, p. (Arg672His), in MYH3 where the phenotypically normal mother is a molecularly confirmed mosaic. To the best of our knowledge, this is the first report in the medical literature of molecularly confirmed parental mosaicism for a MYH3 mutation causing FSS. Since proven somatic mosaicism after having an affected child is consistent with gonadal mosaicism, a significantly increased recurrence risk is advised. Parental testing is thus essential for accurate risk assessment for future pregnancies and the use of new technologies with next generation sequencing (NGS) may improve the detection rate of mosaicism. © 2016 Wiley Periodicals, Inc.